FINANCIAL TECHNOLOGY AND FINANCIAL PERFORMANCE OF DEPOSIT MONEY BANKS IN NIGERIA (Journal of Global Accounting, 2025)
The study determined the effect of financial technology on financial performance of deposit money banks in Nigeria. The study developed three proxies for measuring financial technology which are automated teller machine transactions, mobile banking transaction and point of sale transaction, the study also proxy financial performance using return on investment. The made used of 14 quoted deposit money banks in Nigeria as the population and the study used 10 banks out of the total population as sample size using judgmental sampling techniques to select the sample size. The study adopted ex-post facto research design and used least square regression model. The data used for this study were collected from the Statistical Bulletins of the Central Bank of Nigeria covering the period 2012 - 2023. The result of the analysis of this study shows that automated teller machine transaction has a negative but statistically significant effect on the financial performance of deposit money banks in Nigeria. While Mobile banking transaction and point of sale transactions exerted positive but non-significant effect on return on assets within the period under review. Therefore, the study concludes that, bank management and strategy formulation of banks in Nigeria should take note of negative and significant relationship between value of automated teller machine transactions and return on asset this may suggests that banks may face problems in managing the costs of ATM services. These costs could include maintenance and cash handling, which, if not carefully managed, can pulled down profitability. The study therefore recommend that; Bank management should conduct a comprehensive review of the costs associated with ATM services and implement strategies to optimize the use of ATMs, such as by reducing the number of underutilized machines or enhancing operational efficiencies to reduce costs and improve profitability. The digital banking teams should focus on developing and promoting mobile transaction platforms by increasing user engagement and transaction volumes, as these channels currently have untapped potential.
Keywords: Financial Technology; Automated Teller Machine; Mobile Banking; Point of Sale; Return on Asset